The formation of value orientations of russian and foreign students: axiological aspects - E I Belousova (Peoples' Friendship University of Russia (RUDN University), 2010)
In this paper the theoretical foundations of pedagogical study in the formation of value orientations of Russian and foreign students are carried out. A review of the principles and approaches that provide a basis for determining research directions and concepts of the problem is also being studied.